The autophagy Protein Atg5 Plays a Crucial Role in the Maintenance and Reconstitution Ability of Hematopoietic Stem Cells - Jung, Hi Eun (Immune Netw, 2019)
Hematopoietic stem cells (HSCs) in bone marrow are pluripotent cells that can constitute the hematopoiesis system through self-renewal and differentiation into immune cells and red blood cells. To ensure a competent hematopoietic system for life, the maintenance of HSCs is tightly regulated. Although autophagy, a self-degradation pathway for cell homeostasis, is essential for hematopoiesis, the role of autophagy key protein Atg5 in HSCs has not been thoroughly investigated. In this study, we found that Atg5 deficiency in hematopoietic cells causes survival defects, resulting in severe lymphopenia and anemia in mice. In addition, the absolute numbers of HSCs and multiple-lineage progenitor cells were significantly decreased, and abnormal erythroid development resulted in reduced erythrocytes in blood of Vav_Atg5(−/−) mice. The proliferation of Lin(−)Sca-1(+)c-Kit(+) HSCs was aberrant in bone marrow of Vav_Atg5(−/−) mice, and mature progenitors and terminally differentiated cells were also significantly altered. Furthermore, the reconstitution ability of HSCs in bone marrow chimeric mice was significantly decreased in the presence of Atg5 deficiency in HSCs. Mechanistically, impairment of autophagy-mediated clearance of damaged mitochondria was the underlying cause of the HSC functional defects. Taken together, these results define the crucial role of Atg5 in the maintenance and the reconstitution ability of HSCs.